Learn iPhoto : Mac video training - Garay, Paul (Peachpit Press, 2010)
"Taking the picture is only the beginning! Learn how to import, edit, and share your precious memories using iPhoto 08. Sit back and watch us demonstrate how to get the most from your digital photos and create your own color prints, slide shows, professional greeting cards, personalized calendars and even publish your own hard-cover coffee-table photo book. Most importantly, we will show you how to safeguard your priceless images using iPhoto's built-in backup and archive software."--Resource description page.